Human Epididymis Protein 4 (HE4) as a Serum Tumor Biomarker in Patients With Ovarian Carcinoma. Issue 5 (1st July 2011) - Chang, Xiaohong; Ye, Xue; Dong, Li; Cheng, Hongyan; Cheng, Yexia; Zhu, Lirong; Liao, Qinping; Zhao, Yang; Tian, Li; Fu, Tianyun; Chen, Jun; Cui, Heng
Abstract : Background: Ovarian cancer remains a leading cause of death from gynecological malignancy. Early diagnosis is the most important determinant of survival. For more than 25 years, cancer antigen 125 (CA 125) has been the criterion standard biomarker for the diagnosis and management of women with epithelial ovarian cancer. This study evaluated human epididymis protein 4 (HE4), a novel ovarian cancer biomarker, both alone and in combination with CA 125 as a diagnostic marker for ovarian cancer in a Chinese population. Methods: Sera from 491 Chinese women with ovarian cancer or nonmalignant disorders and healthy women were analyzed. Sensitivities and specificities for both biomarkers and the combination were determined using predefined cutoffs (HE4 >150 pmol/L and CA 125 >35 U/mL) and receiver operator characteristic curves to define cutoffs based on 95% and 98% sensitivities. Results: At baseline, serum HE4 and CA 125 levels were significantly higher in the ovarian cancer group versus the 5 reference groups. Using predefined cutoffs, HE4 specificity for ovarian cancer ranged from 90% to 100%; CA 125 specificity ranged from 36% (benign gynecologic disease) to 99%. Combining both markers yielded specificity for ovarian cancer of 100%. Using receiver operator characteristic curve analysis, the cutoff for 95% and 98% specificity was 102.6 and 150.2 pmol/L for HE4, respectively, and 127.2 and 325.5 U/mL for CA 125, respectively; the sensitivity of CA 125 for distinguishing ovarian cancer from benign gynecologic disease was 54% (95% specificity) and 28% (98% specificity), improving to 78% and 68%, respectively, with the addition of HE4. Conclusions: Human epididymis protein 4 used in conjunction with CA 125 yields improved specificity for ovarian cancer compared with the use of CA 125 alone, generally similar to results seen in non-Chinese populations.